2016
DOI: 10.1038/lsa.2016.133
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast laser processing of materials: from science to industry

Abstract: Processing of materials by ultrashort laser pulses has evolved significantly over the last decade and is starting to reveal its scientific, technological and industrial potential. In ultrafast laser manufacturing, optical energy of tightly focused femtosecond or picosecond laser pulses can be delivered to precisely defined positions in the bulk of materials via two-/multi-photon excitation on a timescale much faster than thermal energy exchange between photoexcited electrons and lattice ions. Control of photo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
497
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 1,029 publications
(506 citation statements)
references
References 174 publications
1
497
0
8
Order By: Relevance
“…A variety of laser-made structures and their applications have been summarized in reviews covering the topic [24,25]. By using critical point drying (CPD), which allows the elimination of capillary forces in the wet development of laser exposed polymers, it is now possible to reliably fabricate 3D structures with 100 nm structural units in 3D, as demonstrated for photonic crystals [26]. Another recent example, in which focused ultra-short laser pulses are used is controllable formation of defects inside the volume of crystals to engineer single photon emitters [27] or to tailor the photo-conductivity of dielectrics for the THz band [28,29].…”
Section: Towards 3d Nano-fabricationmentioning
confidence: 99%
“…A variety of laser-made structures and their applications have been summarized in reviews covering the topic [24,25]. By using critical point drying (CPD), which allows the elimination of capillary forces in the wet development of laser exposed polymers, it is now possible to reliably fabricate 3D structures with 100 nm structural units in 3D, as demonstrated for photonic crystals [26]. Another recent example, in which focused ultra-short laser pulses are used is controllable formation of defects inside the volume of crystals to engineer single photon emitters [27] or to tailor the photo-conductivity of dielectrics for the THz band [28,29].…”
Section: Towards 3d Nano-fabricationmentioning
confidence: 99%
“…All these photomodifi cation mechanisms occur simultaneously and affect polymerization, which takes approximately a millisecond for common photoresists [ 38 ] at a >90% voxel overlap at typical writing velocity of 100 µm s -1 for widespread laser 3D nanolithography. [ 39 ] In this paper, a systematic analysis via modeling and experiments is presented in order to reveal polarization effects, their infl uence on the feature size (resolution), and the coupling between thermal gradient and polarization in DLW.To study and demonstrate the polarization effects, 3D suspended resolution bridges at various angles, α , between the linear polarization and scanning direction were fabricated on a glass substrate ( Figure 1 inset in (a); see details in the Experimental Section). The line-width difference was 10%-20% (varying exposure) under typical polymerization conditions for the linearly polarized pulses.…”
mentioning
confidence: 99%
“…To date, only direct laser writing based 3DLL was shown to be capable of true 3D manufacture at the microscale. This additive manufacturing technique [35] combines a complete freedom of architecture of produced structures [36], possibility to integrate it on various substrates [37][38][39] and a large range of materials that can be processed in such fashion [40]. Here we have shown that structures produced out of zirconium containing photopolymer SZ2080 can withstand a relatively low intensity I = 86.6 W/cm 2 short wavelength exposure for prolonged time periods.…”
Section: Discussionmentioning
confidence: 82%